2003
DOI: 10.1073/pnas.0932534100
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient loading and consumers: Agents of change in open-coast macrophyte assemblages

Abstract: Human activities are significantly altering nutrient regimes and the abundance of consumers in coastal ecosystems. A field experiment in an open-coast, upwelling ecosystem showed that small increases in nutrients increased the biomass and evenness of tide pool macrophytes where consumer abundance and nutrient loading rates were low. Consumers, when abundant, had negative effects on the diversity and biomass of macrophytes. Nutrient loading increases and consumers are less abundant and efficient as wave exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 64 publications
4
72
2
Order By: Relevance
“…Our study demonstrated that the relationship and position of the ABC curves can imply a pollution response within benthic algal assemblages. Inde- Ambient nutrients grazers present < grazers absent Elevated nutrients grazers present = grazers absent Grazers present elevated nutrients = ambient nutrients Grazers absent elevated nutrients < ambient nutrients Anthropogenic increases in nutrient loading promotes rapid growth of opportunistic algae and a decline of more complex canopy-forming algae (Worm & Sommer 2000, Nielsen 2003, Gorgula & Connell 2004. As such, smaller fast-growing species typically dominate polluted environments (McClanahan 1997) and are considered 'weedy', proliferating in conditions unfavourable to more complex species (Tilman & Lehman 2001).…”
mentioning
confidence: 99%
“…Our study demonstrated that the relationship and position of the ABC curves can imply a pollution response within benthic algal assemblages. Inde- Ambient nutrients grazers present < grazers absent Elevated nutrients grazers present = grazers absent Grazers present elevated nutrients = ambient nutrients Grazers absent elevated nutrients < ambient nutrients Anthropogenic increases in nutrient loading promotes rapid growth of opportunistic algae and a decline of more complex canopy-forming algae (Worm & Sommer 2000, Nielsen 2003, Gorgula & Connell 2004. As such, smaller fast-growing species typically dominate polluted environments (McClanahan 1997) and are considered 'weedy', proliferating in conditions unfavourable to more complex species (Tilman & Lehman 2001).…”
mentioning
confidence: 99%
“…These processes are involved in three main benthic-pelagic pathways. First, delivery of nutrients for benthic micro-and macroalgae, as well as plankton and particulate matter for filter feeders, critically depends upon coastal processes and initiates strong bottom-up influences in benthic communities (Menge et al 1997;Nielsen 2003;Wieters 2005). Second, dispersal and subsequent recruitment of species with pelagic larval stages to benthic populations are largely driven by the interaction between larval behavior and physical transport processes (Siegel et al 2008).…”
mentioning
confidence: 99%
“…However, N. helminthoides did not show any physiological improvement when these peaks occurred (in terms of internal nutrient content, protein pools and phycobilins), although it grew and sporulated successfully during the summer, which suggests that it did actually benefit from these pulses. As reported for several macroalgae species growing under transient nutrient pulses (McGlathery, 1992;Barr and Rees, 2003;Costanzo et al, 2000;Nielsen, 2003), the nutrient requirements for sustaining maximum growth and high reproductive effort are usually higher than the mean nutrient availability, even in areas where nutrient background levels exceed those reported in this study (McGlathery, 1992;Borum, 1996, 1997;Phil et al, 1996;Fong et al, 1998;Barr and Rees, 2003;Nielsen, 2003). This nutrient restriction implies that the nutrient uptake during pulses is directly diverted into growth and reproduction (Fong et al, 1994;Vergara et al, 1995), which might explain the lack of short-term physiological responses in N. helminthoides.…”
Section: Discussionmentioning
confidence: 89%
“…These nutrients are mainly provided in the form of transient pulses. However, the physiological response may depend greatly on the nutrient storage capability of the species at short time scales (Vergara et al, 1995;McGlathery, 1996;Pedersen and Borum, 1996;Costanzo et al, 2000;Nielsen, 2003;Bracken, 2004;Clavier et al, 2005;Lartigue and Sherman, 2005).…”
Section: Introductionmentioning
confidence: 99%